POTENSI KONSEP MATEMATIKA DALAM PEMILIHAN DUTA PERTANIAN KALIMANTAN BARAT - Constanius Putra Bepa; Dede Suratman; Bistari Bistari (UNIVERSITAS TANJUNGPURA, 2021)
Mathematics is a science that is always used by humans throughout their lives. In the selection of the West Kalimantan Agricultural Ambassador, we will look for the concept of activities related to mathematics concepts and implementation with school mathematics. Using a descriptive method, because the purpose of this study is to describe the mathematical concepts contained in the selection of the West Kalimantan Agricultural Ambassador. Researchers conducted interviews with 4 sources. It aims to obtain data related to the selection of the West Kalimantan Agricultural Ambassador. From the results of the interview, the researcher digs up information about the preparation, implementation and closing activities. There is a mathematical concept in the third, the aspect of selecting the West Kalimantan Agricultural Ambassador.